THE INFLUENCE OF BUDGET TARGET CLARITY AND ACCOUNTING CONTROL ON THE PERFORMANCE ACCOUNTABILITY OF GOVERNMENT AGENCIES WITH REPORTING SYSTEM AS A MEDIATING VARIABLE - Maharani, Silvia; Husni, Mohamad; Anggriawan, Muhammad Angga; Sari, Gema Ika (Yayasan Education and Social Center, 2025)
This study explores the influence of budget target clarity and accounting controls on government agency performance accountability, with the reporting system as a mediating variable, particularly in the Serang City Government. The purpose of this study is to identify the direct and indirect influences of these variables on government agency performance accountability, with the reporting system serving as a mediating variable. The method used is Structural Equation Modeling - Partial Least Squares (SEM-PLS) with a quantitative approach, involving 76 respondents from various OPDs in the Serang City Government. The results of the study indicate that budget target clarity has a positive and significant influence on the reporting system (β = 0.646; t = 6.811; p = 0.000), and affects government agency performance accountability (β = 0.236; t = 2.476; p = 0.014). Accounting control has a significant positive effect on the reporting system (β=0.323; t=3.309; p=0.001), and affects the accountability of government agency performance (β=0.135; t=2.189; p=0.029). The reporting system itself has a positive and significant effect on government agency performance accountability (β = 0.634; t = 5.817; p = 0.000). In addition, clarity of budget targets and accounting controls has a significant effect on government agency performance accountability through the reporting system, with coefficient values β = 0.410 (t = 4.042; p = 0.008) and β = 0.205 (t = 3.340; p = 0.001). This study provides important insights for improving accountability for government agency performance in the Serang City Government by emphasizing the importance of clarity in budget targets and adequate accounting controls. Thus, efforts to improve these two aspects, supported by a reliable reporting system, can significantly improve the quality of accountability and transparency of government agency performance.